Sex differences in heart failure. (4th December 2019) - Lam, Carolyn S P; Arnott, Clare; Beale, Anna L; Chandramouli, Chanchal; Hilfiker-Kleiner, Denise; Kaye, David M; Ky, Bonnie; Santema, Bernadet T; Sliwa, Karen; Voors, Adriaan A
Abstract: The overall lifetime risk of heart failure (HF) is similar between men and women, however, there are marked sex differences in the landscape of this condition that are both important and under-recognized. Men are predisposed to HF with reduced ejection fraction (HFrEF), whereas women predominate in HF with preserved ejection fraction (HFpEF). Sex differences are also notable in the penetrance of genetic cardiomyopathies, risk factors, e.g. breast cancer which may be associated with cancer treatment-induced cardiomyopathy, as well as sex-specific conditions such as peripartum cardiomyopathy (PPCM). This review outlines the key sex differences with respect to clinical characteristics, pathophysiology, and therapeutic responses to HF treatments. Finally, we address important differences in the prognosis of HF. A central hypothesis is that the higher risk of HFrEF in men compared to women may be attributable to their predisposition to macro vascular coronary artery disease and myocardial infarction, whereas coronary micro vascular dysfunction/endothelial inflammation has been postulated to play a key role in HFpEF and maybe the common link among HF syndromes that women are predisposed to Takotsubo cardiomyopathy, PPCM, and breast cancer radiotherapy-induced cardiomyopathy. Under-pinning current sex disparities in HF, there is a paucity of women recruited to HF clinical trials (20–25% of cohorts) and thus treatment guidelines are predominantly based on male-derived data. Large gaps in knowledge exist in sex-specific mechanisms, optimal drug doses for women and sex-specific criteria for device therapy.